The Influence of Financial Attitude, Financial Socialization, and Financial Experience to Financial Management Behavior with Financial Literacy as the Mediation Variable - Ameliawati, M; Setiyani, R (KnE Social Sciences, 2018)
The purpose of this research is to know whether there is influence of financial attitude, financial socialization, and financial experience to financial management behavior either directly or through financial literacy as mediation variable. The population of this research is the students of Faculty of Economics, State University of Semarang in the year 2015 amounted to 910 students and sampling of 278 students based on Slovin’s formula. The sample technique using incidental sampling. This study uses a quantitative approach. Method of collecting data by using questioner. Data analysis techniques using path analysis. The results of this study indicate (1) there is a positive influence of financial attitude toward financial management behavior (2) there is positive influence of financial socialization to financial management behavior (3) there is positive influence of financial experience to financial management behavior (4) there is positive influence financial literacy to financial management behavior (5) there is positive influence of financial attitude toward financial literacy (6) there is positive influence of financial socialization to financial literacy (7) there is positive influence of financial experience to financial literacy (8) there is positive influence of financial attitude toward financial management behavior through financial literacy (9) there is positive influence of financial socialization to financial management behavior through financial literacy (10) there is positive influence of financial experience to financial management behavior through financial literacy. Keywords: Financial Attitude, Financial Socialization, Financial Experience, Financial Management Behavior, Financial Literacy